2008
DOI: 10.1038/nmat2292
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected power-law stress relaxation of entangled ring polymers

Abstract: After many years of intense research, most aspects of the motion of entangled polymers have been understood. Long linear and branched polymers have a characteristic entanglement plateau and their stress relaxes by chain reptation or branch retraction, respectively. In both mechanisms, the presence of chain ends is essential. But how do entangled polymers without ends relax their stress? Using properly purified high-molar-mass ring polymers, we demonstrate that these materials exhibit self-similar dynamics, yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

51
857
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(910 citation statements)
references
References 43 publications
(66 reference statements)
51
857
1
1
Order By: Relevance
“…Some viscosity studies suggested that N c for rings is smaller than that of linear polymers, 3,4,6 but simulation results argued that N c for rings would be about two to five times higher than that of linear chains, 15 or even much larger. 17 Moreover, by demonstrating the self-similar dynamics of purified high-molarmass ring polymers, Kapnistos et al 24 even questioned the existence of N c for ring polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some viscosity studies suggested that N c for rings is smaller than that of linear polymers, 3,4,6 but simulation results argued that N c for rings would be about two to five times higher than that of linear chains, 15 or even much larger. 17 Moreover, by demonstrating the self-similar dynamics of purified high-molarmass ring polymers, Kapnistos et al 24 even questioned the existence of N c for ring polymers.…”
Section: Introductionmentioning
confidence: 99%
“…properties of ring polymers in the ring-linear blends. [24][25][26][27][28][29][30][31] Iyer et al 28 proposed a scaling model on the size of ring polymers in ring-linear blend and found that by gradually increasing the composition of linear chains, the ring molecules swell, with Flory's scaling exponent v increasing from 0.4 to 0.5 in the limit of infinite dilution for the rings. Using the BFM, Subramanian and Shanbhag 29,30 studied the dynamics of entangled ring polymers in ring-linear blends and found the self-diffusion coefficient and the primitive path length of ring polymers are more sensitive to volume fraction than that of linear chains.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ring polymers possess a closed contour, which leads to markedly different relaxation and diffusion mechanisms. Recently, there has been much improvement in the production of purified systems of rings (6)(7)(8), with the consequent result that more and more experimental puzzling evidence requires a deeper understanding of their motion in concentrated solutions and melts from a theoretical point of view.…”
mentioning
confidence: 99%
“…On the other hand, numerical and experimental findings (5,6) suggest that rings exhibit strong intercoil correlations, which have proved difficult to address in simplified theoretical models (9)(10)(11)(12). Because of this, there have been many recent attempts to rigorously characterize these interchains' interactions (13)(14)(15)(16), although a precise definition and unambiguous identification of these "threadings" in concentrated solutions of rings remains elusive.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Recently, commendable achievements have been experienced with the control of polymer properties by mixing polymers with linear and nonlinear architectures. Particular examples are tuning of domain spacing, 16 micellar morphologies, 17 and viscoelasticity, 18 and preparation of miscible blends with a Additional Supporting Information may be found in the online version of this article. combination of inherently immiscible polymers.…”
mentioning
confidence: 99%